Perjanjian Asuransi Modern dalam Hukum Islam - Sofhian Sofhian (Al-Ulum, 2010)
This paper explores some thoughts on modern insurance in the study of Islamic law. Also the commercialized insurance agreement in implementation which is classified haram according to Islamic law. And, the social-oriented insurance in order to create social welfare is acceptable of Islamic shari'ah. The concept of insurance is prohibited in the Islamic shari'ah is the concept of insurance in the treaty should be based on Ã¢â‚¬Å“aqad takafuliÃ¢â‚¬Â or mutual help and in easing the burden or unprecedented risk, which is also called the "Kafal deed".